2011
DOI: 10.1111/j.1365-2567.2011.03426.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte perforin and Fas ligand working in concert even when Fas ligand lytic action is still not detectable

Abstract: Summary The reason(s) why individual cytotoxic T lymphocytes (CTL) possess a fast‐acting, perforin/granzyme‐mediated, as well as a much slower, Fas ligand (FasL) ‐driven killing mechanism is not clear, nor is the basis for wide variations in killing activity exhibited by individual CTL, ranging from minutes to hours. We show that perforin expression among individual, conjugated CTL varies widely, which can account for the heterogeneity in killing speeds exhibited by individual CTL. Despite a 2‐hr lag in FasL‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 40 publications
4
69
0
3
Order By: Relevance
“…However, we noted in subsequent in vivo studies that while FasL-deficient CD8 + T cells exhibited impaired cytotoxicity of alloprimed IgG1 + B cells, as compared to wild-type CD8 + T cells, perforin-deficient CD8 + T cells exhibited moderate levels of cytotoxicity. Our results are consistent with a recent report indicating that perforin-mediated CD8 + T cell cytotoxicity is inhibited in the absence of FasL, suggesting that perforin-mediated cytotoxicity requires the presence of FasL for efficient killing (38). Alternatively, CD8 + T cells may utilize perforin to downregulate antibody production in other ways, in addition to killing B cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, we noted in subsequent in vivo studies that while FasL-deficient CD8 + T cells exhibited impaired cytotoxicity of alloprimed IgG1 + B cells, as compared to wild-type CD8 + T cells, perforin-deficient CD8 + T cells exhibited moderate levels of cytotoxicity. Our results are consistent with a recent report indicating that perforin-mediated CD8 + T cell cytotoxicity is inhibited in the absence of FasL, suggesting that perforin-mediated cytotoxicity requires the presence of FasL for efficient killing (38). Alternatively, CD8 + T cells may utilize perforin to downregulate antibody production in other ways, in addition to killing B cells.…”
Section: Discussionsupporting
confidence: 93%
“…CD8 T cells can suppress viral spread by the production of interferon‐ γ , by the induction of apoptosis via the cell surface receptors Fas–Fas ligand, and by secreted perforin and granzymes. Several studies have also demonstrated that expression of perforin can serve as a marker of ongoing activation and killing capacity of CD8 T cells . Apart from their positive effects of controlling viral spread, CTL have been shown to cause tissue damage in viral infections, such as in viral myocarditis and viral hepatitis .…”
Section: Introductionmentioning
confidence: 99%
“…Although perforin mediated granzyme B delivery is described as an early event and Fas/FasL induced death is described as occurring late, the only available technologies available to evaluate this activity in real time require sophisticated microchip technology. (17) Additionally, monitoring of cytotoxicity by fluorescence based approaches leads to a relatively low signal to noise ratio, due to background fluorescence from live or fixed cells. We reasoned that a protease-inducible, luminescent biosensor introduced into target cells alone would allow us to measure CTL-induced caspase induction in a living cell continuously, in a convenient, non-radioactive, microplate format with minimal background signal.…”
Section: Introductionmentioning
confidence: 99%